Effect of diode pumping solid state laser with wavelength 589 nm on gene expression of interlukine-2 and interferon-gamma Lowercase in human T-lymphocytes - Marwa Akram Nafe’a; Nibras Hatim Khamees; Mustafa Salih Ali Almusawi (Journal of the Pakistan Medical Association, 2024)
Objective: To evaluate the impact of laser irradiation of human T-cell lymphocyte in culture to determine the photobiomodulatory effects of such irradiation on gene expression, and the release of growth factors and cytokines. Method: The experimental study was conducted from November 2021 to April 2022 at the Postgraduate Anatomy Laboratory, Mustansiriyah University, Baghdad, Iraq, and comprised human blood samples T-cell lymphocytes were extracted and irradiated, followed by the extraction of ribonucleic acid to assess the effect of laser on gene expression of cytokines, interlukine-2 and interferon-gamma. A 589nm yellow light low-level laser beam from a diode pumping solid state laser was used at doses 30J/cm2, 50J/cm2 and 70J/cm2 for an exposure time of 15 minutes. Reverse transcriptase-polymerase chain reaction was used to measure gene expression. Data was analysed using GraphPad Prism 9. Result: Cellular gene expression of the mediators changed significantly in response to laser irradiation at a variety of dosage parameters, and these effects depended on the wavelength and radiation exposure (p<0.05). Conclusion: The laser light may photobiomodulate the production of cytokines by human cells in vitro. Key Words: Interferon, Lasers, Lymphocytes, Gene, Polymerase, Radiation